2001
DOI: 10.1111/j.1471-0528.2001.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of significant pathology in women attending a general gynaecological service for postcoital bleeding

Abstract: Objectives To document the frequency of pathology in women who complain of postcoital bleeding. To determine whether negative cervical cytology excludes serious pathology in women with postcoital bleeding. To determine whether postcoital bleeding increases the risk of serious pathology in women with an abnormal smear.Design A retrospective study.Setting A university teaching hospital. Population 314 women with postcoital bleeding seen in the gynaecology service from ®rst January 1988 to 31 December 1994. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
6
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 6 publications
5
62
6
3
Order By: Relevance
“…16 Shalini R et al reported that 5.5% of women with postcoital bleeding had invasive cancer cervix in their study whereas Rosenthal AN et al reported 4% cases with invasive cancer cervix. 8,9 Allen et al reported that 1% of women with postcoital bleeding had carcinoma cervix in their study and Ashrafgangoei T et al reported 1.8% cases with invasive cancer cervix in women with postcoital bleeding in their study. 19 Sensitivity of papsmear was 71.42%, specificity-86.20%, PPV-78.95%, NPV-80.64% and accuracy-80% in present study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…16 Shalini R et al reported that 5.5% of women with postcoital bleeding had invasive cancer cervix in their study whereas Rosenthal AN et al reported 4% cases with invasive cancer cervix. 8,9 Allen et al reported that 1% of women with postcoital bleeding had carcinoma cervix in their study and Ashrafgangoei T et al reported 1.8% cases with invasive cancer cervix in women with postcoital bleeding in their study. 19 Sensitivity of papsmear was 71.42%, specificity-86.20%, PPV-78.95%, NPV-80.64% and accuracy-80% in present study.…”
Section: Discussionmentioning
confidence: 98%
“…5 The prevalence of cervical cancer in women with post coital bleeding is 3-5.5% and prevalence of CIN is 6.8-17.8%. [6][7][8][9][10] Cervical cancer is the second most common cancer in the women throughout the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Postcoital bleeding should be considered an indication for prompt referral to a colposcopic clinic and a high risk factor for CIN.…”
Section: Observation and Discussionmentioning
confidence: 99%
“…S›kl›kla servikovajinal infeksiyon, inflamasyon, travma, servikal polip, ektropion gibi benign lezyonlara ba¤l› geliflirken, servikal intraepitelyal neoplazi (CIN) ve invaziv karsinomlar›n da belirtisi olabilir (2,3) . Postkoital kanamal› hastalarda invazif karsinom ve CIN prevalans› farkl› çal›flmalarda s›ras›yla %3 -17.8 civar›nda rapor edilmifltir (3)(4)(5)(6)(7)(8)(9) .…”
Section: G‹r‹fiunclassified